Human DNA Extraction by Two Extraction Methods for Forensic Typification from Human Feces on FTA Paper - Sandoval-Arias, Shirleny Monserrat (2014)
The identification of suspects in criminal investigations has been facilitated since DNA test are executed on different samples. The application of this technology for forensic typification from human fecal samples still presents complications therefore this research evaluated two DNA extraction protocols with modifications to determine that of major efficiency. Organic extractions and extractions using the commercial kit “IQTM DNA Casework Sample Kit for Maxwell ® 16” on FTA portions of 4cm2 and 1cm2 impregnated with feces from the same individual were done to accomplish the objective. In all the assays the results were useful, however; the best forensic typification (by the electropherogram characteristics) was obtained by using the commercial kit in an area of 1 cm2 of FTA paper impregnated in a 1:4 dilution.